2017
DOI: 10.3917/spub.175.0611
|View full text |Cite
|
Sign up to set email alerts
|

Évaluation de la perception des facteurs de stress post-accouchement au Gynépôle de Marseille

Abstract: These results encourage implementation of guidelines and the organization of informal ?conversations? in the maternity unit, and to conduct an early postnatal consultation at home for these mothers concerning their childbirth experience, which could be ensured by adequate social support based on empathic listening and reassuring actions about parenting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…These findings are concordant with other studies in the literature showing that parity affects the experience of pregnancy. 12 , 21 Nulliparous women are more desirous of medical support and depend more on healthcare providers, with a greater need for support. Furthermore, it has been shown that nulliparous women fear delivery, particularly in relation with their perception of the pain of a vaginal birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are concordant with other studies in the literature showing that parity affects the experience of pregnancy. 12 , 21 Nulliparous women are more desirous of medical support and depend more on healthcare providers, with a greater need for support. Furthermore, it has been shown that nulliparous women fear delivery, particularly in relation with their perception of the pain of a vaginal birth.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire included 11 questions covering the following: woman’s age, history of prior interrupted pregnancies (SM; voluntary interruption of pregnancy; termination of pregnancy for medical reasons; fetal death in utero; and/or ectopic pregnancy); date of last period; and the intention to pursue the current pregnancy to its term. Seven questions asked about sources of stress during pregnancy, as established in the literature, 12 15 namely the following: level of education and socioeconomic vulnerability; number of previous pregnancies (gravidity); previous number of deliveries (parity); marital difficulties; social or familial isolation; and whether the current pregnancy was unexpected or unplanned.…”
Section: Methodsmentioning
confidence: 99%